Food Loss and Food Waste as Global Issues - Thu, Dao Thi Anh; Loan, Nguyen Thi Truc (Global and Policy Journal of International Relations, 2015)
ABSTRACTThe entire world is facing significant challenges in the coming decades. It has been demonstrated that many countries must prepare themselves to face a considerable rise in food consumption and corresponding food waste. There must be a cooperation of consumers, retailers, producers and government to solve this complex issue. Their efforts to decrease food waste would offer a significant sustainable alternative to scale up food manufacturing that leading to a stabling food security internally and internationally. Governments and businesses should develop food loss and food waste prevention throughout the entire supply chain. There should be a higher effort on decreasing post-harvest losses in early stages in the food value chain in the developing countries. Meanwhile, in the developed countries, the government should have policies to reduce food waste at consumer level which could minimize food being unnecessarily thrown away. Governments should also support the establishment of independent organizations which could facilitate and assess efforts to decrease food waste, such as the WRAP in the UK in grocery and hospitality supply chain.Keywords: food loss, food waste, food value chain, reuse, cycleDOI:https://doi.org/10.33005/jgp.v3i02.1933